Postmortem Evaluation of Autolytic Changes in Morphology of Red Blood Cells and Haemogram Pattern for Estimation of Time since Death (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
The accurate estimation of time since death sometimes is very important for forensic experts in administration of justice. Various cells and tissues of the body showed significant changes with respect to post-mortem interval and one such sample is blood. The aim of this study is to assess the post-mortem autolytic changes in morphology of red blood cells and haemogram pattern for estimation of time since death. The present study was a cross sectional one and non random purposive sampling was done. The blood samples from 60 dead bodies which were brought for postmortem examination in the mortuary and preserved in
Keywords: Autolytic changes; Haemogram; Peripheral blood smear; Red blood cell morphology; Time since death; Post-mortem interval